IMPLEMENTASI KURIKULUM MERDEKA DAN IMPLIKASINYA TERHADAP MUTU PENDIDIKAN PESANTREN - Hoerul Umam; Aep Saepullah; Abdul Latip (STKIP Subang, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum in Islamic boarding school (pesantren) educational institutions and its implications for improving educational quality. As a national education policy, the Merdeka Curriculum introduces a new learning paradigm that emphasizes flexibility, character development, literacy, numeracy, and student-centered learning. On the other hand, pesantren, as the oldest Islamic educational institution in Indonesia, possesses a distinctive tradition of tafaqquh fi al-din and a value-based educational system deeply rooted in Islamic teachings and community life.This study employed a descriptive qualitative approach using a library research method by examining policy documents, academic journals, books, and previous studies related to the implementation of the Merdeka Curriculum and pesantren education. The findings reveal that the implementation of the Merdeka Curriculum in pesantren can be carried out in an integrative manner while maintaining the identity and distinctive characteristics of pesantren education. This integration is manifested through the incorporation of religious and general sciences within an adaptive and contextual curriculum framework.Furthermore, the implementation of the Merdeka Curriculum has positive implications for improving the quality of pesantren education, particularly in strengthening literacy, character development, creativity, and students’ critical thinking skills. Nevertheless, several challenges remain, including the readiness of human resources, limited educational facilities and infrastructure, and the need for more systematic and professional curriculum management. Therefore, sustainable policy support, intensive training for pesantren educators, and the development of an integrative curriculum model based on pesantren values are essential to ensure the optimal implementation of the Merdeka Curriculum